Historical Institutionalism, Hybridity and Institutional Logics in Public Transport History. Issue 2 (August 2022) - Fowler, James
This paper responds to calls for new theoretical frameworks within which to examine transport history and bring it into contact with other disciplines with a view to overcoming some of its alleged previous preoccupations with Anglocentric economic data. It offers three interconnected ideas from other fields, historical institutionalism, hybridity and institutional logics and it proposes that these tools can assist historians in making sense of the qualitative material from archival records. The paper also suggests that by explicitly framing the history of public transport as a political process, historians can engage with a wider social ecology of interest groups than those represented by economic interests. Whilst recognising the assumptions inherent in an institutional approach and the limitations of the scope of the author's own research, the paper argues that these frameworks can nevertheless be used widely and effectively.